2018
DOI: 10.3390/su10072276
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and the Long-Term Performance of Mergers and Acquisitions: Do Regions and Related-Party Transactions Matter?

Abstract: This study investigates the effects of geographical regions and related-party transactions on corporate social responsibility (CSR) and long-term mergers and acquisitions (M&A) performance linkage. We conduct a Heckman two-stage model analysis, using data from listed firms in the Shanghai and Shenzhen stock exchange markets in China. The results indicate that: (1) buyers' CSR performance has a significant and positive effect on long-term M&A performance. (2) Significant differences exist across geographical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…We used the variable “east region” and made it serve as a method variance marker. East region is a dummy variable to indicate different market environments in different regions of China (Qiao et al. , 2018), which is theoretically unrelated to other scales in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We used the variable “east region” and made it serve as a method variance marker. East region is a dummy variable to indicate different market environments in different regions of China (Qiao et al. , 2018), which is theoretically unrelated to other scales in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Qiao et al [41] examined the effects of geographical regions and related party transactions on CSR and long-term M&A performance interactions in China. They found that the acquirer's CSR performance significantly positively affected long-term M&A performance.…”
Section: Effects Of Csr On Manda Activitiesmentioning
confidence: 99%
“…Yen and André's [11] study main limitation is the lack of ownership information for multiple companies, which impeded the testing of typical agency problems in emerging markets. Due to the large gaps in market development, regulations, and CSR awareness, the conclusions of Qiao et al [41] were drawn for China's listed firms, which might not be applicable to all M&As in China or in developed countries.…”
Section: Effects Of Csr On Manda Activitiesmentioning
confidence: 99%
“…However, research is lacking on the validity of measuring CSR performance and disclosure quality, as well as the convergent validity between these scores. In this paper, a comparative and quantitative analysis was performed for the period 2010-2017, and the following results were obtained: (1) Based on a comparison of the rating methods, information sources, and other factors, RKS is more suitable for measuring the CSR disclosure quality, while Hexun is more suitable for measuring the CSR performance; (2) based on a Spearman correlation analysis, the convergent validity between these two scores is very low, particularly after 2013; and (3) the sub-indicator weights of the RKS system always maintain a high stability, whereas those of the Hexun system suffer from severe fluctuations starting in 2013.Sustainability 2019, 11, 3921 2 of 20 mechanisms of economic consequences [20][21][22][23], the drivers of CSR performance [24][25][26][27][28][29], and economic consequences [30][31][32][33][34][35]; and (2) the HX score is used only as a proxy for the CSR performance level, such as in research on the drivers of CSR performance [36][37][38][39][40] and the economic consequences of CSR performance [19,33,[41][42][43]. Some studies even use the level-1 sub-indicator of the HX score, the environmental dimension HXE, to score a firm's environmental performance level [44,45].Sustainability 2019, 11, x FOR PEER REVIEW 2 of 21 also for CSR performance levels, such as in research on the drivers of CSR disclosure quality [16][17][18][19], the mechanisms of economic consequences [20][21]…”
mentioning
confidence: 99%
“…Sustainability 2019, 11, x FOR PEER REVIEW 2 of 21 also for CSR performance levels, such as in research on the drivers of CSR disclosure quality [16][17][18][19], the mechanisms of economic consequences [20][21][22][23], the drivers of CSR performance [24][25][26][27][28][29], and economic consequences [30][31][32][33][34][35]; and (2) the HX score is used only as a proxy for the CSR performance level, such as in research on the drivers of CSR performance [36][37][38][39][40] and the economic consequences of CSR performance [19,33,[41][42][43]. Some studies even use the level-1 sub-indicator of the HX score, the environmental dimension HXE, to score a firm's environmental performance level [44,45].…”
mentioning
confidence: 99%